Determinan Jumlah Uang Beredar, Tingkat Bunga, dan Inflasi Terhadap Pertumbuhan Ekonomi Indonesia - Adya Utami (Al-Buhuts, 2019)
This study aims to determine the determinants of the money supply, the interest rate, and inflation on Indonesia's economic growth in the 2009-2018 period. This research uses descriptive method and is strengthened by the OLS (ordinary least square) method with secondary data. The data used is sourced from the Central Statistics Agency and Bank Indonesia. The results of this study indicate that the money supply and the interest rate have a negative effect but inflation has a positive effect on Indonesia's economic growth. The JUB variable is not significant with a probability value of 0.1326. The JUB regression coefficient value has a negative relationship to the economic growth variable with a coefficient of 0.9288. The interest rate variable entered in the above equation turns out to be negative and significant with a probability value of 0.0571. The value of the coefficient of the exchange rate is (0.4843). The independent variable inflation gives a negative and not significant result with a probability value of 0.1134. Inflation coefficient value is 0.1724. In the equation model that uses economic growth as the dependent variable above, the magnitude of the coefficient of determination (R Squared) is 0.573429. This shows that the ability of the independent variable in explaining the diversity of the independent variables is 57.34% while the remaining 42.66% is influenced by other variables not included in the model.